Enhanced external counterpulsation and short-term recovery from high-intensity interval training - Valenzuela, P. L.; Sánchez-Martínez, G.; Torrontegi, E.; Montalvo, Z.; Lucia, A.; de la Villa, P. (International Journal of Sports Physiology and Performance, 2018)
Purpose: Enhanced external counterpulsation (EECP) is a recovery strategy whose use has increased in recent years owing to the benefits observed in the clinical setting in some cardiovascular diseases (ie, improvement of cardiovascular function). However, its claimed effectiveness for the enhancement of exercise recovery has not been analyzed in athletes. The aim of this study was to determine the effectiveness of EECP on short-term recovery after a fatiguing exercise bout. Methods: Twelve elite junior triathletes (16 [2] y) participated in this crossover counterbalanced study. After a high-intensity interval training session (6 bouts of 3-min duration at maximal intensity interspersed with 3-min rest periods), participants were assigned to recover during 30 min with EECP (80 mm Hg) or sham (0 mm Hg). Measures of recovery included performance (jump height and mean power during an 8-min time trial), metabolic (blood lactate concentration at several time points), autonomic (heart-rate variability at several time points), and subjective (rating of perceived exertion [RPE] and readiness to compete) outcomes. Results: There were no differences between EECP and sham in mean RPE or power output during the high-intensity interval training session, which elicited a significant performance impairment, vagal withdrawal, and increased blood lactate and RPE in both EECP and sham conditions (all P<.05). No significant differences were found in performance, metabolic, or subjective outcomes between conditions at any time point. A significantly lower high-frequency power (P<.05, effect size=1.06), a marker of parasympathetic activity, was observed with EECP at the end of the recovery phase. Conclusion: EECP did not enhance short-term recovery after a high-intensity interval training session in healthy, highly trained individuals.